Zakat menjadi Instrumen dalam Mewujudkan Stabilitas Perekonomian - Asnaini Asnaini (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
Zakat that is managed properly and professionally will support the formation of economic conditions that grow with equity, increase productivity accompanied by equal distribution of income and increase employment for the community. Potential as a source of spending in Muslim communities, a source of funds to overcome various kinds of social costs caused by human relations, and able to build economic growth as well as the inclusion of income economic growth with equity. This will indirectly prevent usury practices, create economic cooperation, and social security, and most importantly can lift the economy of weak people which has an impact on maintaining economic stability. This is where the importance of the role of the state in the management of zakat lies, so that economic, social, and educational functions in Zakat obligations can be realized.